Refinement of cortical dysgeneses spectrum associated with TUBA1A mutations. Issue 10 (26th August 2008) - Bahi-Buisson, N; Poirier, K; Boddaert, N; Saillour, Y; Castelnau, L; Philip, N; Buyse, G; Villard, L; Joriot, S; Marret, S; Bourgeois, M; Van Esch, H; et al.
Abstract : Objective: We have recently shown that de novo mutations in the TUBA1A gene are responsible for a wide spectrum of neuronal migration disorders. To better define the range of these abnormalities, we searched for additional mutations in a cohort of 100 patients with lissencephaly spectrum for whom no mutation was identified in DCX, LIS1 and ARX genes and compared these data to five previously described patients with TUBA1A mutations. Results: We detected de novo TUBA1A mutations in six patients and highlight the existence of a prominent form of TUBA1A related lissencephaly. In four patients, the mutations identified, c.1190T>C (p.L397P), c.1265G>A (p.R422H), c.1264C>T (p.R422C), c.1306G>T (p.G436R), have not been reported before and in two others, the mutation corresponds to a recurrent missense mutation, c.790C>T (p.R264C), likely to be a hot spot of mutation. All together, it emerges that the TUBA1A related lissencephaly spectrum ranges from perisylvian pachygyria, in the less severe form, to posteriorly predominant pachygyria in the most severe, associated with dysgenesis of the anterior limb of the internal capsule and mild to severe cerebellar hypoplasia. When compared with a large series of lissencephaly of other origins (ILS17, ILSX or unknown origin), these features appear to be specific to TUBA1A related lissencephaly. In addition, TUBA1A mutated patients share a common clinical phenotype that consists of congenital microcephaly, mental retardation and diplegia/tetraplegia. Conclusions: Our data highlight the presence of consistent and specific abnormalities that should allow the differentiation of TUBA1A related lissencephalies from those related to LIS1, DCX and ARX genes.